2020
DOI: 10.3390/s20154068
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Individual Exposure to Erythemal Weighted UVR by Multi-Sensor Measurements and Integral Calculation

Abstract: Ultraviolet radiation (UVR) can be hazardous to humans, especially children, and is associated with sunburn, melanoma, and the risk of skin cancer. Understanding and estimating adults’ and children’s UVR exposure is critical to the design of effective interventions and the production of healthy UVR environments. Currently, there are limitations to the ways computer modeling and field measurements estimate individual UVR exposure in a given landscape. To address these limitations, this study developed an approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Additionally, the abundance of local shading and varying levels of shade seeking behaviour are (respectively) environmental and individual factors that lower doses and can vary substantially, but that our model does not yet account for due to a lack of information [11,34,51,52]. Our model assumes that subjects are fully exposed for the entire duration of their exposure period when, in reality, builders and skiers could find themselves on slopes that are topographically shaded, and builders especially could be occasionally shaded by foliage, structures, or even their colleagues and vehicles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the abundance of local shading and varying levels of shade seeking behaviour are (respectively) environmental and individual factors that lower doses and can vary substantially, but that our model does not yet account for due to a lack of information [11,34,51,52]. Our model assumes that subjects are fully exposed for the entire duration of their exposure period when, in reality, builders and skiers could find themselves on slopes that are topographically shaded, and builders especially could be occasionally shaded by foliage, structures, or even their colleagues and vehicles.…”
Section: Resultsmentioning
confidence: 99%
“…On hot days, people will naturally seek such shade more so than on cold days. Additionally, recent research has found that dosimeters are prone to underestimating doses when subject to complex environmental shading such as man-made canopies [52]. By not accounting for any level of environmental shading or individual shade-seeking behaviour, our approach can overestimate doses, but it is not clear if this over-estimation is significant here as the original study for the builders data specifically chose locations with a lack of shade to avoid these issues [39] and most ski slopes are not shaded.…”
Section: Resultsmentioning
confidence: 99%
“…This work is also intended to serve this purpose. A classification is therefore difficult and can only be compared with modelling [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…We found that modelled personal UVR exposure (based on a combination of self‐reported time spent outdoors and ambient UVR levels) and self‐reported time outdoors were equally good and better predictors of measured personal UVR exposure than ambient UVR. Previous studies 9,11–13 exploring UVR exposure modelling approaches include an algorithm (Genesis‐UV) to retrospectively estimate lifetime occupational exposure, and a 3D numeric model (SimUVex/SimUVex v2) that estimates site‐specific erythemal doses received at an individual level; therefore, it is not possible to compare their findings with ours. However, our observation that self‐reported time outdoors and a modelling approach could better predict measured personal UVR exposure compared with the ambient UVR is in line with our previous simulation study, 6 which showed that ambient UVR alone could explain only 16% of the variability in the annual measured personal UVR exposure whereas self‐reported time spent outdoors along with ambient UVR increased the explained variation to 40%.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the available evidence evaluating the validity of the aforementioned surrogates of UVR exposure is still limited, with few studies validating UVR exposure modelling approaches 9,11–13 . Moreover, studies comparing validity of different surrogates of long‐term UVR exposure are nonexistent.…”
mentioning
confidence: 99%